2016
DOI: 10.3343/alm.2016.36.5.441
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Vaginal Microbiome by Next-Generation Sequencing and Evaluation of its Performance as a Clinical Diagnostic Tool in Vaginitis

Abstract: BackgroundNext-generation sequencing (NGS) can detect many more microorganisms of a microbiome than traditional methods. This study aimed to analyze the vaginal microbiomes of Korean women by using NGS that included bacteria and other microorganisms. The NGS results were compared with the results of other assays, and NGS was evaluated for its feasibility for predicting vaginitis.MethodsIn total, 89 vaginal swab specimens were collected. Microscopic examinations of Gram staining and microbiological cultures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 19 publications
1
35
0
1
Order By: Relevance
“…While previous studies have focused on the vaginal and cervical microbiome, it may be useful to investigate the perinatal, uterine, and ovarian microbiomes as well. Consideration of fungal species in such studies may also yield interesting results. Future microbiome research into inflammation and carcinogenesis certainly promises to provide unique and interesting insights into health and disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies have focused on the vaginal and cervical microbiome, it may be useful to investigate the perinatal, uterine, and ovarian microbiomes as well. Consideration of fungal species in such studies may also yield interesting results. Future microbiome research into inflammation and carcinogenesis certainly promises to provide unique and interesting insights into health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…As in the gut microbiome, higher diversity in the vaginal microbiome is correlated with increased incidence of inflammatory conditions, in this case candidal vulvovaginitis or bacterial vaginosis . In bacterial vaginosis, there is a reduction in Lactobacillus and an increase in the abundance of other bacteria such as Prevotella . Once the bacterial vaginosis is treated with antibiotics, the vaginal microbiome becomes less diverse, with increasing frequency of lactobacilli .…”
Section: The Vaginal Microbiomementioning
confidence: 99%
“…Comprehensive studies on healthy human vaginal microbiome have identified Lactobacillus spp. to be the dominant bacterial species by both culture-dependent and -independent methods [110][111][112][113]. Although absolute numbers vary, due to different endogenous and exogenous conditions (age, lifestyle, pregnancy, hormone levels, etc.…”
Section: A Role For the Microbiome?mentioning
confidence: 99%
“…To our knowledge, this is the rst evaluation of this association using next-generation sequencing. Previous studies investigated the association of the vaginal microbiome with menopause (31), perinatal outcome (32), preterm birth (33), sexually transmitted diseases (34), vaginitis (30), HPV (35), and urinary tract infections (36). No study has evaluated the relationship of the vaginal microbiome with environmental pollutants in young females with impaired ovarian function.…”
Section: Discussionmentioning
confidence: 99%